Umphred's neurological rehabilitation - Rolando T. Lazaro; Reina-Guerra, Sandra G.; Quiben, Myla U. (St. Louis, Missouri : Elsevier, 2020)
"Develop problem-solving strategies for individualized, effective neurologic care! Under the new leadership of Rolando Lazaro, Umphred's Neurological Rehabilitation, 7th Edition, covers the therapeutic management of people with activity limitations, participation restrictions, and quality of life issues following a neurological event. This comprehensive reference reviews basic theory and addresses the best evidence for evaluation tools and interventions commonly used in today's clinical practice. It applies a time-tested, evidence-based approach to neurological rehabilitation that is perfect for both the classroom and the clinic. Now fully searchable with additional case studies through Student Consult, this edition includes updated chapters and the latest advances in neuroscience."--Provided by publisher
Foundations of clinical practice -- Movement analysis across the life-span -- Contemporary issues and theories of motor control, motor learning, and neuroplasticity -- The limbic network: Influence over motor control, memory, and learning -- Psychosocial aspects of adaptation and adjustment during various phases of neurological disability -- Differential diagnosis of the patient with a neurological condition -- Examination and evaluation of functional movement activities, body functions and structures, and participation -- Interventions for individuals with movement limitations -- Medical and developmental challenges of infants in neonatal intensive care: management and follow-up considerations -- Management of clinical problems of children with cerebral palsy -- Genetic disorders: a pediatric perspective -- Learning disabilities and developmental coordination disorder -- Spina bifida: A neural tube defect -- Traumatic spinal cord injury -- Neuromuscular diseases -- Beyond the central nervous system: neurovascular entrapment syndromes -- Multiple sclerosis -- Disorders of the basal nuclei -- Cerebellar dysfunction -- Balance dysfunction -- Vestibular dysfunction -- Traumatic brain injury -- Concussion -- Movement dysfunction associated with hemiplegia -- Brain tumors -- Inflammatory and infectious disorders of the brain -- Aging, dementia, and disorders of cognition -- Disorders of vision and visual-perceptual dysfunction -- Cardiovascular and pulmonary system health in populations with neurological disorders -- Pain management -- Electrophysiological testing and electrical stimulation in neurological rehabilitation -- Orthotics: Evaluation, intervention, and prescription -- Integrating health promotion and wellness into neurorehabilitation -- Human immunodeficiency virus infection: living with a chronic illness -- Aging with chronic nervous system conditions and impairments -- Impact of drug therapy on patients receiving neurological rehabilitation -- Use of neuroimaging in rehabilitation -- Integrating technology in neurological rehabilitation -- Complementary and integrative therapies: beyond traditional approaches to intervention in neurological diseases and movement disorders.
Includes index.
Keywords: Nervous system -- Diseases -- Physical therapy; Nervous system -- Diseases -- Patients -- Rehabilitation; Nervous System Diseases -- rehabilitation